2005
DOI: 10.1038/sj.npp.1300657
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acamprosate and Neramexane on Cue-Induced Reinstatement of Ethanol-Seeking Behavior in Rat

Abstract: This study examines, for the first time, the effects of acamprosate and the non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist neramexane on ethanol-seeking induced by alcohol-related environmental stimuli in an animal model of relapse. Wistar rats were trained to operantly self-administer ethanol (10% w/v) or water on a fixed-ratio 1 schedule in a 30-min daily session. Ethanol availability was signaled by an olfactory discriminative stimulus of orange extract (S þ ). In addition, each lever press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
18

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 58 publications
5
61
0
18
Order By: Relevance
“…Acamprosate and naltrexone, FDA-approved medications that promote abstinence in alcohol abusers [24,25 ], dose-dependently attenuate ethanol seeking in response to the S + /CS + without altering responding to the S − /CS − [23,26 ]. These findings support the predictive validity of this paradigm, as a model of cue-induced ethanol relapse.…”
Section: Drug-predictive Discriminative Stimulus (S + )-Induced Reinssupporting
confidence: 70%
“…Acamprosate and naltrexone, FDA-approved medications that promote abstinence in alcohol abusers [24,25 ], dose-dependently attenuate ethanol seeking in response to the S + /CS + without altering responding to the S − /CS − [23,26 ]. These findings support the predictive validity of this paradigm, as a model of cue-induced ethanol relapse.…”
Section: Drug-predictive Discriminative Stimulus (S + )-Induced Reinssupporting
confidence: 70%
“…Reinstatement of alcohol-seeking is used to study the neurobiological and molecular basis of craving, as there appears to be a good correspondence between the events that induce alcohol-seeking in laboratory animals and those that provoke craving in humans (Shaham et al, 2003). In a previous study, it was shown that acamprosate completely abolishes the cue-induced reinstatement response (Bachteler et al, 2005). As described in this previous report, the calcium salt of N-acetylhomotaurinate (acamprosate) abolished the reinstatement response but equimolar concentration of the corresponding sodium salt formulation of acamprosate had no effect (Figure 4).…”
Section: Na-aota Is Ineffective In Preclinical Animal Models But Calcmentioning
confidence: 99%
“…Extinction of ethanol-reinforced responding was performed as previously described for rats (Bachteler et al, 2005) and mice (Tsiang and Janak, 2006). After mice responded on the RR8 schedule for 16 weeks, the animals were exposed to 30-min extinction sessions during which both levers were extended and the house light remained illuminated.…”
Section: Extinction Of Ethanol-reinforced Respondingmentioning
confidence: 99%